Pesquisas sobre a educação de tempo integral no contexto do Programa Mais Educação: 2010 a 2017 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This study has as object of the scenario of research on full-time education in Brazil, in the context of the More Education Program. In this regard, the problem that guided the research was centered on the question: how does the scenario research on full-time education in Brazil, in the context of the More Education Program (2010-2017) is characterized? As a general objective, we sought to analyze research on full-time education in Brazil, in the context of the More Education Program (2010-2017), based on the approach of the Epistemologies of Educational Policy (EEPE). The study is anchored on meta-research as a possibility of addressing and analyzing research in education policy, carried out from the EEPE approach, based on the referential of Mainardes, Ferreira and Tello (2011), Tello and Mainardes (2012), Tello (2013), Tello and Mainardes (2015), Mainardes and Tello (2016), Stremel and Mainardes (2016), Mainardes, Stremel and Soares (2018), and Mainardes (2017, 2018, 2018). Using the EEPE approach, we identified in the researches selected as data the epistemological perspective, the epistemological positioning, and the epistemological focus. Regarding the epistemological aspect of the analyzed productions, we understand that, in a half, they work with the epistemological perspective of educational policy as a theoretical and knowledge field, in a Pluralist perspective. Concerning the epistemological positioning, we identified that the researchs reveal a critical-analytical character of the study of the Mais Educação Program policy, as well as of the researched realities. The epistemological approach identified revealed a qualitative study approach and as types of research the bibliographic research, the documentary research, and the field research. Through this study, we found that the the scenario of research on full-time education in Brazil, in the context of the More Education Program, presented the largest number of productions in the year 2017, indicating a rising number of works. The researchs emerged mostly from the Southeast region, justified by the link with groups and lines of research coming from this region. With the study, we also observed that the researchs stress the Mais Educação Program policy, showing its contradictions, such as insufficient human and financial resources and precarious infrastructure, which do not allow the proposal to be implemented with enough quality.
Keywords: Educação de Tempo Integral; Programa Mais Educação; Teses e dissertações; Full-time Education; More Education Program; Theses and Dissertations; CNPQ::CIENCIAS HUMANAS::EDUCACAO